Solution of the direct problem in turbid media with inclusions using Monte Carlo simulations implemented in graphics processing units: New criterion for processing transmittance data - Carbone, Nicolás Abel (2010)
The study of light propagation in diffusive media requires solving the radiative transfer equation, or eventually, the diffusion approximation. Except for some cases involving simple geometries, the problem with immersed inclusions has not been solved. Also, Monte Carlo MC calculations have become a gold standard for simulating photon migration in turbid media, although they have the drawback large processing times. The purpose of this work is two-fold: first, we introduce a new processing criterion to retrieve information about the location and shape of absorbing inclusions based on normalization to the background intensity, when no inhomogeneities are present. Second, we demonstrate the feasibility of including inhomogeneities in MC simulations implemented in graphics processing units, achieving large acceleration factors, thus providing an important tool for iteratively solving the forward problem to retrieve the optical properties of the inclusion. Results using a cw source are compared with MC outcomes showing very good agreement.